Diversion for Children as Perpetrators of Theft (A Study of Case Decision Number 27/Pid.Sus.Anak/2023/PN Jkt.Utr) - Tri Nova Aini (DE RECHT (Journal of Police and Law Enforcement), 2026)
Children continue to be involved as perpetrators of theft in Indonesia, even though Law Number 11 of 2012 on the Juvenile Justice System obliges the pursuit of diversion as a legal protection mechanism for children. In practice, however, the application of diversion is not always consistent, as illustrated by Case Decision Number 27/Pid.Sus.Anak/2023/PN Jkt.Utr, in which two children were sentenced to imprisonment despite formally satisfying the requirements for diversion. This study aims to analyze the judges' considerations in that decision from the perspective of diversion as a form of legal protection for children. The study employs a normative legal research method, applying a statutory approach and a case approach, with data collected through library research and analyzed descriptively. The findings show that although the requirements for diversion under Article 7 of Law Number 11 of 2012, namely a statutory threat of imprisonment under seven years and the absence of repeat offending, were satisfied, diversion was not pursued through to the trial stage before the District Court. A comparison with Case Decision Number 37/Pid.Sus.Anak/2024/PN Srg indicates that the divergence in outcome stems primarily from the extent to which each panel of judges actively pursued diversion, rather than from any fundamental difference in the underlying facts. This study recommends more consistent application of diversion at every stage of the juvenile justice process to fulfill the protective purpose that the law already sets out to achieve.